2013
DOI: 10.1186/1471-2180-13-294
|View full text |Cite
|
Sign up to set email alerts
|

Non-essential genes form the hubs of genome scale protein function and environmental gene expression networks in Salmonella entericaserovar Typhimurium

Abstract: BackgroundSalmonella Typhimurium is an important pathogen of human and animals. It shows a broad growth range and survives in harsh conditions. The aim of this study was to analyze transcriptional responses to a number of growth and stress conditions as well as the relationship of metabolic pathways and/or cell functions at the genome-scale-level by network analysis, and further to explore whether highly connected genes (hubs) in these networks were essential for growth, stress adaptation and virulence.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…In brief, since pncA is believed to be nonessential (40), mutations may confer low to no fitness cost, resulting in no selective pressure on the functional protein, which in turn can result in mutations occurring anywhere in the gene without a loss of fitness. However, it has been shown previously that although a gene may be considered nonessential in vitro, it may be essential in vivo (87,88). From the protein science point of view, it is difficult to imagine how mutations scattered all over the enzyme and away from the active site can render the enzyme dysfunctional.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, since pncA is believed to be nonessential (40), mutations may confer low to no fitness cost, resulting in no selective pressure on the functional protein, which in turn can result in mutations occurring anywhere in the gene without a loss of fitness. However, it has been shown previously that although a gene may be considered nonessential in vitro, it may be essential in vivo (87,88). From the protein science point of view, it is difficult to imagine how mutations scattered all over the enzyme and away from the active site can render the enzyme dysfunctional.…”
Section: Discussionmentioning
confidence: 99%
“…One study using myocardial data from 1617 samples found that known foetal gene markers upregulated in gene networks common to developing and diseased myocardium were not hub genes [ 79 ]. Another co-expression study in Salmonella found that hub genes are dispensable for growth, stress adaptation and virulence, suggesting that hub genes are not necessarily essential [ 80 ].…”
Section: Clustering and Network Analysismentioning
confidence: 99%
“…Salmonella , like several other Gamma-proteobacteria, are found in various environments including soils, water systems, and sewage, as well as in the gut flora of various animals. To survive and multiply in this large variety of environments, their metabolism has to adapt well (Rosenkrantz et al, 2013 ). The large genome of Salmonella contains more than 4000 genes encoding a large range of metabolic pathways, for instance an S .…”
Section: Introductionmentioning
confidence: 99%
“…Rosenkrantz et al ( 2013 ) compared two types of networks for S . Typhimurium strain LT2 regarding stress response and metabolic adaptation: a transcriptional data network using transcriptional data for 425 selected genes under different growth and stress conditions identifying the significantly and strongly regulated genes (transcriptional network) for each condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation